Orbital metastases in breast cancer - Viola Alles, Alberto; Etchebarne, Liliana; Musé, Miguel; Pacheco, Héctor (Cirugía del Uruguay, 1984)
The symptomatology and evolution of 4 patients with unilateral orbital metastases due to mammary cancer are analyzed. Three of same appeared posteriorily to the primitive tumor and the other was posterior.